2021
DOI: 10.1002/adfm.202101494
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Ionogel Paint from Room‐Temperature Autonomous Polymerization of α‐Thioctic Acid for Stretchable and Healable Electronics

Abstract: Development of a universal stretchable ionic conductor coating on insulating substrates, irrespective of surface chemistry and substrate shapes, is of immense interest for compliant and integrative large‐area electronics but has proved to be extremely challenging. Existing methods relying either on the concurrent deposition of polymerizing precursors or on divided formulation and painting processes both suffer from several limitations in terms of adhesion, dehydration, processability, and surface pre‐treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
131
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(133 citation statements)
references
References 58 publications
2
131
0
Order By: Relevance
“…This phenomenon of energy dissipation is commonly observed in many gel systems with noncovalent interactions. [17,34,35] With an increase of tensile strain, the hysteresis area and hysteresis ratio of the loading-unloading cycles both increased (Figure S14, Supporting Information). These results indicated that more noncovalent bonds in the ionogel network were destroyed as the strain increased, which dissipated more energy and triggered more structural change.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…This phenomenon of energy dissipation is commonly observed in many gel systems with noncovalent interactions. [17,34,35] With an increase of tensile strain, the hysteresis area and hysteresis ratio of the loading-unloading cycles both increased (Figure S14, Supporting Information). These results indicated that more noncovalent bonds in the ionogel network were destroyed as the strain increased, which dissipated more energy and triggered more structural change.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Figure 3e shows the stretchability and durability of the recently reported hydrogel-, organohydrogel-and ionogel-based ionic conductors. [10][11][12][13][14][19][20][21][24][25][26][27][28][29][30][31]34,35,[49][50][51][52][53][54][55][56][57][58] Our VPVA 40% -IL ionic conductors are at record levels in terms of their stretchability and durability, demonstrating their considerable potential for use in flexible electronics and devices.…”
Section: Durability and Healability Of The Vpva 40% -Il Ionic Conductorsmentioning
confidence: 99%
“…[21] Meanwhile, there has also been a growing interest to explore soft polymeric hydrogels for flexible sensors. [22][23][24][25][26][27][28][29][30][31][32] Different from elastomers, polymeric hydrogels usually have a 3D crosslinked hydrophilic network that is highly swollen by water. [5,33] Thus they are endowed with many unique advantages, including intrinsic soft wet nature, good biocompatibility, and especially tissue-like mechanical properties, which have made polymeric hydrogels promising candidates for flexible sensors.…”
mentioning
confidence: 99%